AC and DC power transfer optimization research using numerical models for wireless heavy-duty EV charging - Mustafa Karavus; Ahmet Arif Ergin; Gulten Polat; Bunyamin Esiyok (Bulletin of Electrical Engineering and Informatics, 2026)
Wireless power transfer (WPT) can enable automated charging of heavy-duty electric vehicles (HDEVs), where high power levels require high efficiency and stable operation. This paper compares AC- and DC-based WPT architectures for the TEMSA LD SB E bus using MATLAB/Simulink simulations. The anal ysis is conducted at three operating frequencies (80, 85, and 90 kHz) and for coupling coefficients ranging from 0.10 to 0.90 with 0.10 increments. The AC system uses an eight-switch resonant inverter, whereas the DC system employs a direct DC/DC converter. Transient behavior is solved using a fourth-order Runge–Kutta scheme, and electromagnetic interactions are verified via finite element analysis (FEM). Peak efficiencies of 96.10% (AC) and 97.44% (DC) are achieved at 85 kHz and a coupling coefficient of 0.90. Normalized sensi tivity indices and linear regression identify coupling and frequency as dominant factors, while the DC architecture exhibits reduced sensitivity. The results pro vide quantitative guidance for designing reliable high-power WPT chargers for commercial fleets.